2022
DOI: 10.9734/jocamr/2022/v17i430340
|View full text |Cite
|
Sign up to set email alerts
|

Justicia secunda Leaf Aqueous Fraction Suppressed NF-κB, TNF-α, IL-6, and COX-2 in Arthritic Rat

Abstract: Aims: This study evaluated the effect of the aqueous fraction of Justicia secunda Vahl leaves on selected inflammatory markers Tumor necrosis factor alpha (TNF-α), nuclear factor–kappa B (NF-κB), interleukin-6 (IL-6) and cyclooxygenase-2 (COX-2) and its possible mechanism of action. Study Design: J. secunda aqueous leaf fraction (JSALF) was tested on carrageenan, arachidonic and Complete Freund’s Adjuvant (CFA) induced rat paw inflammation models, respectively. Methodology:  Ninety male albino rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…They concluded that PHZ-induced haemolytic anaemia stimulated the production of pro-inflammatory cytokines, such as TNF-α, IL-2 and interferon-γ, which might play a role in the immune response to haemolysis. Furthermore, in this study, the hydromethanol extract of J. secunda caused a significant decrease in TNF-α, which is in correlation with a report by Kings-Ogbonna and Anyasor,[ 24 ] which reported there was a significant ( P < 0.05) decrease in serum levels of TNF-α, IL-6 and COX-2 in J. secunda leaf aqueous fraction treated rats compared with untreated control animals. This decrease could be linked to its anti-inflammatory properties, as reported by Onoja et al .…”
Section: Discussionsupporting
confidence: 92%
“…They concluded that PHZ-induced haemolytic anaemia stimulated the production of pro-inflammatory cytokines, such as TNF-α, IL-2 and interferon-γ, which might play a role in the immune response to haemolysis. Furthermore, in this study, the hydromethanol extract of J. secunda caused a significant decrease in TNF-α, which is in correlation with a report by Kings-Ogbonna and Anyasor,[ 24 ] which reported there was a significant ( P < 0.05) decrease in serum levels of TNF-α, IL-6 and COX-2 in J. secunda leaf aqueous fraction treated rats compared with untreated control animals. This decrease could be linked to its anti-inflammatory properties, as reported by Onoja et al .…”
Section: Discussionsupporting
confidence: 92%